Two Saporin-Containing Immunotoxins Specific for CD20 and CD22 Show Different Behavior in Killing Lymphoma Cells - Polito, Letizia; Mercatelli, Daniele; Bortolotti, Massimo; Maiello, Stefania; Djemil, Alice; Battelli, Maria; Bolognesi, Andrea (Toxins, 2017)
Immunotoxins (ITs) are hybrid proteins combining the binding specificity of antibodies with the cytocidal properties of toxins. They represent a promising approach to lymphoma therapy. The cytotoxicity of two immunotoxins obtained by chemical conjugation of the plant toxin saporin-S6 with the anti-CD20 chimeric antibody rituximab and the anti-CD22 murine antibody OM124 were evaluated on the CD20-/CD22-positive cell line Raji. Both ITs showed strong cytotoxicity for Raji cells, but the anti-CD22 IT was two logs more efficient in killing, probably because of its faster internalization. The anti-CD22 IT gave slower but greater caspase activation than the anti-CD20 IT. The cytotoxic effect of both immunotoxins can be partially prevented by either the pan-caspase inhibitor Z-VAD or the necroptosis inhibitor necrostatin-1. Oxidative stress seems to be involved in the cell killing activity of anti-CD20 IT, as demonstrated by the protective role of the H2O2 scavenger catalase, but not in that of anti-CD22 IT. Moreover, the IT toxicity can be augmented by the contemporary administration of other chemotherapeutic drugs, such as PS-341, MG-132, and fludarabine. These results contribute to the understanding of the immunotoxin mechanism of action that is required for their clinical use, either alone or in combination with other drugs.